Artemis Fowl : the last guardian - Colfer, Eoin. (New York : Disney/Hyperion Books, 2012)
Opal Koboi after reanimating fairy warriors from thousands of years in the past, plans to destroy all human life on Earth, unless Artemis Fowl teen genius, can stop her, and the Fowl Estate is ground zero for the battle.
7.2
5-8
Keywords: Fowl, Artemis (Fictitious character) -- Juvenile fiction; Space and time -- Juvenile fiction; Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Genius -- Juvenile fiction; Fowl, Artemis (Fictitious character) -- Fiction; Space and time -- Fiction; Fairies -- Fiction; Magic -- Fiction; Genius -- Fiction; Fantasy fiction; Adventure and adventurers -- Fiction; Fowl, Artemis (Fictional character) -- Fiction; Space and time -- Fiction; Fairies -- Fiction; Magic -- Fiction; Genius -- Fiction; Fantasy fiction; Adventure fiction; Fantasy fiction; Adventure fiction